Sustainability Does Not Begin With the Individual - Hazas, Mike; Brush, A.J.; Scott, James (Interactions, 2012)
In the past decade, an increasing amount of HCI research has been concerned with making personal and household environmental impacts (such as energy, water, or CO2 equivalents) more visible, with the aim of educating people and affecting their relevant actions. We have two concerns with this. First, when evaluated “in the wild,” the scale of reduction achieved tends to be limited to less than 10 percent (of, say, household electricity or water) and is not proven to be long-lasting. This result is the same as for interventions trialed over the past four decades, many of which employed low-tech methods such as itemized or more frequent energy bills [1].